Slide attacks and LC-weak keys in T-310. Issue 3 (4th May 2019) - Courtois, Nicolas T.; Georgiou, Marios; Scarlata, Matteo
Abstract: T-310 is an important Cold War cipher (Cryptologia 2006). In a recent article (Cryptologia 2018), researchers show that, in spite of specifying numerous very technical requirements, the designers do not protect the cipher against linear cryptanalysis and some 3% of the keys are very weak. However, such a weakness does not necessarily allow breaking the cipher because it is extremely complex and extremely few bits from the internal state are used for the actual encryption. In this article, we finally show a method that allows recovering a part of the secret key for about half of such weak keys in a quasi-realistic setting. For this purpose, we revisit another recent article from Cryptologia from 2018 and introduce a new peculiar variant of the decryption oracle slide attack with d = 0.